Focal Dystonia in Musicians [Distonía Focales en Los Músicos] - Chana-Cuevas, P; Alburquerque-Gonzalez, D (2011)
Introduction: A special group of focal dystonia is that known as occupational, which include dystonic disorders triggered by repetitive motor activity, closely associated with the professional activity of a specific task that the affected person performs. In this sense, musicians are a population particularly vulnerable to this disorder, which is presented during the execution of highly trained movements. Objective: This article reviews the pathophysiology of focal dystonia and its therapeutic implications. Development: The pathophysiological basis of focal dystonia in the musician is still not well established. However, due to the contribution of neurophysiological studies and functional neuroimaging, there is growing evidence of anomalies in the processing of sensory information, sensory-motor integration, cortical and subcortical inhibitory processes, which underline this disease.Clinically, it is characterised by the appearance of involuntary muscle contractions, and is associated with loss of motor control while practicing music. It is a gradual appearance and sometimes there may be a history of musculoskeletal injuries or non-physiological postures preceding the appearance of the symptoms. The neurological examination is usually normal, although subtle dystonic postures can develop spontaneously or with movements that involve the affected segments. The dystonia remains focal and is not generalised. Conclussions: Treatment is based on using multiple strategies for the management of the dystonia, with variable results. Although a specific therapy has not been defined, there are general principles that are combined in each situation looking for results. This includes, among others, pharmacological interventions, management with botulinum toxin, and sensory re-training techniques. © 2010 Sociedad Española de Neurología.